2022
DOI: 10.1111/jdv.18292
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ‐based quantitative proteomics reveals biomarkers/pathways in psoriasis that can predict the efficacy of methotrexate

Abstract: Background Methotrexate (MTX) is the first‐line medicine to treat psoriasis. So far, there has been less research on protein biomarkers to predict its efficacy by the proteomic technique. Objectives To evaluate differentially expressed proteins in peripheral mononuclear cells (PBMCs) between good responders (GRs) and non‐responders (NRs) after MTX treatment, compared with normal controls (NCs). Methods We quantified protein expression of PBMCs with four GRs and four NRs to MTX and four NCs by isobaric tags for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…In short, platelet activation promotes IL‐17 production by releasing microparticles and forming aggregates with inflammatory cells [49, 51, 52], which further induces platelet activation and contributes to psoriasis development [53]. Our proteomics data indicated that MTX treats psoriasis by modulating neutrophil degranulation and platelet activation, inhibiting the NF‐κB and JAK–STAT pathways [54]. Other studies reported that MTX suppresses T lymphocytes by upregulating negative co‐stimulatory molecules [55].…”
Section: Discussionmentioning
confidence: 83%
“…In short, platelet activation promotes IL‐17 production by releasing microparticles and forming aggregates with inflammatory cells [49, 51, 52], which further induces platelet activation and contributes to psoriasis development [53]. Our proteomics data indicated that MTX treats psoriasis by modulating neutrophil degranulation and platelet activation, inhibiting the NF‐κB and JAK–STAT pathways [54]. Other studies reported that MTX suppresses T lymphocytes by upregulating negative co‐stimulatory molecules [55].…”
Section: Discussionmentioning
confidence: 83%
“…Although L-ELK1, but not S-ELK1, significantly upregulated neutrophil activity-related signals (Fig. 5 C), we also found that S-ELK1 significantly upregulated the expression of several neutrophil activity-related genes, including GSN, CTSB, CPNE3 [ 41 ], RAP2B [ 42 ], FCGR2A [ 43 ], HPSE [ 44 ], and modestly upregulated ANXA2, ANXA3 [ 45 ], MOSPD2 [ 46 ], GNS [ 47 ], SDCBP [ 48 ], PAGM1 [ 49 ], HEXB [ 50 ], LAPM2 [ 51 ], STOM [ 52 ], and CR1 [ 53 ] (Fig. 6 A).…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, circulating pathogenic cytokine levels were found to be reduced after methotrexate treatment [ 76 ], as well as lesional chemokine CXCL12 levels [ 77 ], contrary to the upregulated IL-4 interleukin [ 76 ]. Hypothesis-free proteomic analyses have been additionally employed to identify response biomarkers and elucidate the mechanism of action of methotrexate, confirming the molecular reversion of deregulated proteins after administration [ 78 ]. Qiu et al were the first to perform a comprehensive gut microbiome profiling in methotrexate-treated psoriasis patients, attempting to correlate post-treatment microbiome alterations with the blood metabolome [ 79 ].…”
Section: Traditional Therapiesmentioning
confidence: 99%